THE CHILDREN AND YOUTH CREATIVITY SCHOOL (SEKAR): PREVENTIVE SOCIAL INNOVATION FOR CHILDREN OF INDONESIAN MIGRANT WORKER - Ashlihul Hayati; Ratnasari Putri Utami (Progress In Social Development, 2026)
The high number of Indonesian Migrant Workers (PMI) has contributed to complex socio-economic challenges in Compreng Village, Subang Regency, including limited parental care among children left behind. In 2023–2024, 327 residents were recorded as migrant workers, affecting more than 200 children and increasing their risk of psychosocial vulnerability. This study examines the Purnama Subang Program, focusing on the Children and Youth Creativity School (SEKAR) as a preventive social innovation. Using a qualitative case study approach, data were collected through observation, in-depth interviews with children, caregivers, and facilitators, and document analysis. The analysis is guided by Attachment Theory and Self-Determination Theory. The findings indicate that SEKAR functions as a community-based safe space that provides complementary caregiving, psychosocial support, and capacity development. Participation in creative activities and migration literacy enhances children’s self-confidence, learning autonomy, and social relationships. Facilitators also serve as alternative attachment figures that strengthen emotional security. SEKAR demonstrates strong potential as a scalable model to mitigate the intergenerational impacts of parental migration.